Biological Activity of the Soil and Microbial Dynamics - Zarqum Rahimov Zafarjonzoda (Genius Journals, 2023)
The microbiological activity of soils determines the transformation, migration and accumulation of matter, energy and information in the soil. The mass of microorganisms in the soil and especially the mass of plant litter processed by them is comparable to the mass of the litter itself. This determines the role of microorganisms as a factor in soil formation. It is shown that the composition of microorganisms and their weight are indicators of ongoing processes of soil formation, cultivation and degradation of soils. Thus, in the weakly cultivated and well cultivated soddy-podzolic soil in the Ap horizon, the content of microorganisms developing on MPA was 1118 and 1975 thous./1 g, those developing on KAA was 3306 and 3598 thous./1 g of soil. The content of microorganisms developing on MPA in summer was 0.91 million/1 g in the solonetz; in light chestnut soil - 1.42 million/1 g, developing on KAA - 0.79 and 2.8 million/1 g of soil.
Keywords: soil formation; microorganisms; soil cultivation; seasonal dynamics